واقع وآفاق السياسات المالية والنقدية في البلدان النامية - صقر, محمد; ديوب, محمد معن; غدير, هيفاء غدير (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يقدم هذا البحث دراسة عن اقتصاديات البلدان النامية، من خلال طرح مجموعة من الخصائص العامة التي تتسم بها اقتصاديات هذه البلدان، لنجد أن أهم ما تعانيه هي حلقة الفقر المفرغة الناجمة عن انخفاض الدخل القومي الذي يؤدي إلى انخفاض مستوى الادخار وإلى انخفاض مستوى الاستثمار، وهذا ما يؤدي بدوره إلى استمرار انخفاض الدخل. كما أنه يبين الصفات العامة التي تتصف بها السياسات المالية والنقدية والتي تظهر ضعف النظام الضريبي فيها، لنجد أن الضرائب لا تأخذ دورها الفعال بالإضافة إلى اعتمادها على القروض العامة وعجز الموازنة، تلك الأدوات التي تؤثر سلبياً على الاقتصاد، وذلك لوجود ضعف وعدم مرونة في أجهزته الإنتاجية، بالإضافة إلى اعتماد اقتصاديات هذه البلدان على الأدوات الكيفية في السياسات النقدية أكثر من الأدوات الكمية التي تحتاج إلى بنية تحتية مناسبة لتقوم بعملها على الوجه الأمثل من أجهزة مالية ومصرفية إلى أسواق مالية متطورة. كما نقوم بعرض التطور المالي لمنطقة الشرق الأوسط وشمال أفريقيا بكونها جزءاً من البلدان النامية لنعرض التحديات التي تواجه صانعي السياسات في تلك البلدان في ظل ما يسمى بالعولمة واقتصاد السوق. This research provides a study of the economics of the developing countries by giving a group of general specifications of the economics of these countries. It concludes that the prominent problem for these countries is the problem of poverty as a result of the decrease of the national income that leads to the decline in the level of savings, which in turns lead to the decrease in the level of investment and consequently to the continuating of decline of the income. It also shows the general characteristics of the financial and monetary policies in the developing countries, which show the weakness of their taxation system .Taxes don’t take their active role. Moreover developing countries depend on the public loans and budget deficit, the tools that affect the economy negatively because of the weakness and inflexibility of its productive devices, in addition of the dependence of the economics of these countries on the qualitative tools of the monetary policies more than the quantitative tools that need a suitable infrastructure of monetary and bank facilities and a developed capital market to do their job properly. We will also trance the financial development in the Middle East region and North Africa as part of the developing countries to show the challenges that face the policies makers in these countries under what is called globalization and market economy.